Characterization of Cypermethrin-degradation by a Novel Molybdenum-reducing Morganella sp. Isolated from Active Agricultural Land in Northwestern Nigeria (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2021)
The increasing use of cypermethrin in agricultural fields, household and industrial applications for effective pest control had increased the global burden of the pollutant over the years. Consequently, there is an urgent need to devise techniques to eliminate this pollutant from the environment. A bacterium capable of degrading cypermethrin has been successfully screened and characterized. The bacterium was grown in a mineral salt medium (MSM) supplemented with cypermethrin as its sole carbon and energy source at an optimum pH 7.5, temperature 40 ÂºC, a carbon source concentration of 4 g/L, optimum incubation time of 24 h and an inoculum size of 400 ÂµL. The potential of Morganella sp. to degrade cypermethrin makes it an important instrument for the degradation of cypermethrin. This knowledge may be useful for the optimization of environmental conditions for cypermethrin bioremediation and important for detoxification of cypermethrin polluted sites.
Keywords: Cypermethrin; Molybdenum-reducing; Pollutant; Morganella sp.; Bioremediation